2005
DOI: 10.1007/s11104-004-2389-3
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of sugar mill by-products compost with N2-fixing bacteria

Abstract: Inoculation of sugar mill by-products compost with N 2 -fixing bacteria may improve its quality by increasing total N and available P. Compost was inoculated with Azotobacter vinelandii (ATCC 478), Beijerinckia derxii (ATCC 49361), and Azospirillum sp. TS8, each alone and all three together. Numbers of all N 2 -fixing bacteria in compost declined from an initial population of 5 · 10 5 cells g )1 during incubation. The population of Azotobacter declined to approximately 2 · 10 2 cells g )1 and the population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Plants inoculated with N 2 -fixing bacteria may have increased growth because the bacteria fix N, (Kumar and Narula, 1999;Kumar and Singh, 2001), and/or provide plant growth hormones (Amooaghaie et al, 2002;Bashan and Holguin, 1997;Bashan and Levanomy, 1990;Lin et al, 1983). Additionally our previous research (Meunchang et al, 2005b) had suggested that The treatment not receiving compost was included in the analysis of variance for comparative purposes. inoculated compost resulted in 10% higher rates of organic matter mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plants inoculated with N 2 -fixing bacteria may have increased growth because the bacteria fix N, (Kumar and Narula, 1999;Kumar and Singh, 2001), and/or provide plant growth hormones (Amooaghaie et al, 2002;Bashan and Holguin, 1997;Bashan and Levanomy, 1990;Lin et al, 1983). Additionally our previous research (Meunchang et al, 2005b) had suggested that The treatment not receiving compost was included in the analysis of variance for comparative purposes. inoculated compost resulted in 10% higher rates of organic matter mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculated compost showed significant acetylene reduction activity during the composting process and up to 16% increase in total N content (Meunchang et al, 2005b) indicating that the inoculant bacteria were capable of N fixation and may have provided some additional N to the plants. However, the role of increased N mineralization in the soil cannot be ruled out in our study and deserves additional study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the above mentioned diverse and usually bench scale utilities of the substrate Meunchang et al (2005) have rightly commented that one of the under utilized sources of organic materials, is the sugarcane industry. Global sugar production from sugarcane releases large amounts of sugar mill by-products as filter cake and bagasse.…”
Section: Sugarcane Bagasse-a Resource Rather Than a Wastementioning
confidence: 99%